Speciation, adsorption and determination of chromium(III) and chromium(VI) on a mesoporous surface imprinted polymer adsorbent by combining inductively coupled plasma atomic emission spectrometry and UV spectrophotometry. Issue 24 (20th November 2013) - Liu, Yan; Meng, Xiangguo; Han, Juan; Liu, Zhanchao; Meng, Minjia; Wang, Yun; Chen, Rui; Tian, Sujun
<x xml:space="preserve">Abstract</x> In the present study, a Cr(III)‐imprinted polymer (Cr(III)‐IIP) was prepared by an easy one‐step sol–gel reaction with a surface imprinting technique on the support of silica mesoporous material. A new SPE method for the speciation, separation, preconcentration, and determination of Cr(III) and Cr(VI) by inductively coupled plasma atomic emission spectrometry and UV on the mesoporous‐imprinted polymer adsorbent was developed. The structure of the imprinted polymer was characterized by Fourier transform infrared spectroscopy, X‐ray powder diffraction, transmission electron microscopy, and nitrogen adsorption–desorption isotherms. The adsorption kinetics, thermodynamics behavior, and recognition ability toward Cr(III) on Cr(III)‐IIP and nonimprinted polymer were compared. The results showed that Cr(III)‐IIP had higher selectivity and nearly a two times larger Langmuir adsorption capacity (38.50 mg/g) than that of NIP. The proposed method has been successfully applied in the determination and speciation of chromium in natural water samples with satisfactory results.